Radix Astragalus Polysaccharide Accelerates Angiogenesis by Activating AKT/eNOS to Promote Nerve Regeneration and Functional Recovery - Zhang, Geyi; Huang, Jinsheng; Hao, Shuang; Zhang, Jingchao; Zhou, Nan (Frontiers in Pharmacology, 2022)
Peripheral nerve injury (PNI) results in loss of neural control and severe disabilities in patients. Promoting functional nerve recovery by accelerating angiogenesis is a promising neuroprotective treatment strategy. Here, we identified a bioactive Radix Astragalus polysaccharide (RAP) extracted from traditional Chinese medicine (TCM) as a potent enhancer of axonal regeneration and remyelination. Notably, RAP promoted functional recovery and delayed gastrocnemius muscle atrophy in a rat model of sciatic nerve crush injury. Further, RAP treatment may induce angiogenesis in vivo. Moreover, our in vitro results showed that RAP promotes endothelial cell (EC) migration and tube formation. Altogether, our results show that RAP can enhance functional recovery by accelerating angiogenesis, which was probably related to the activation of AKT/eNOS signaling pathway, thereby providing a polysaccharide-based therapeutic strategy for PNI.